What pet should I get? [compact disc, unabridged] ; & One fish two fish red fish blue fish - Seuss, Dr (Listening Library, 2015)
What pet should I get? This new book by Dr. Seuss about making up one's mind is the literary equivalent of buried treasure! What happens when a brother and sister visit a pet store to pick a pet? Naturally, they can't choose just one! The tale captures a classic childhood moment--choosing a pet--and uses it to illuminate a life lesson: that it is hard to make up your mind, but sometimes you just have to do it! Told in Dr. Seuss's signature rhyming style, this is a must-have for Seuss fans and book collectors, and a perfect choice for the holidays, birthdays, and happy occasions of all kinds.